INVESTMENT ANALYSIS FOR SMALL SCALE LAYER CHICKEN BUSINESS (Case Study in Triwidadi Village Pajangan Sub District Bantul Yogyakarta) - Rini Widiati; Sudi Nurtini; Suci Paramitasari Syahlani; Bambang Ariyadi (Buletin Peternakan, 2017)
Chicken eggs are the most popular and nutritious food in human dietary.The production activities require investments that should create benefit for the business holder, especially for small-scale entrepreneurs with capital constraint and risks. The purpose of this study was to determine investment feasibility and to set alternatives in dealing with the risks on the small scale layer business. Survey method was implemented using 73 respondents selected purposively of small scale layer chicken business in Triwidadi village of Bantul district, Yogyakarta as the sample. Data were collected by direct interview to respondents using questionnaires that related to the research problem. Analysis of investment financial feasibility criteria’s using Net Present Value, Benefit Cost Ratio and Internal Rate of Return, followed by sensitivity analysis in facing business risk.  The result revealed that the average number of birds raised was 1572 birds. The NPV was IDR 37,377,383 per 5 years of investment, B / C ratio more than 1 and IRR was 20.58%. Based on the existing production management, layer chicken investment by small-scale farmers was profitable, but farmers faced on the risk of losses due to increasing feed prices, decreasing egg prices, and increased mortality. In anticipating the risks, farmers should improve productivity so that the Hen Day Average of egg production at least was 77%, on the increase in feed prices and decrease in egg prices of 5%. Small scale layer businesses could provide employment and welfare for society of lower classes.